Effect of internal focus of attention with touching cue on the agonist muscle activity during exercise - Oshita, K. (Journal of Human Sport & Exercise, 2021)
This study aimed to investigate the effect of internal focus of attention with touching cue on agonist muscular activity during the arm curl exercise. Ten healthy males (age, 20-35 years) performed five repetitions of arm curl under three different focus instructions: external focus condition (EXT), where participants were instructed to concentrate on lifting the bar; internal focus condition (INT), where participants were instructed to concentrate on contractions of biceps brachii; and, internal focus and touch condition (INT+T): participants' biceps brachii was lightly touched by the investigator and they were instructed to concentrate on muscle contractions at the touched point. Although the average muscular activities in INT and INT+T were significantly higher than that of EXT (p < .01), no significant difference in muscle activity between INT and INT+T was observed. Further, magnitudes of these effects were small (d < 0.25). These results suggest that internal focus caused by individual's consciousness, as well as a focus attention by touching the agonist area increased the agonist muscle activity during exercise. However, the increase in agonist muscle activity due to focus attention is limited.